Reference dosimetry in MRI-linacs: evaluation of available protocols and data to establish a Code of Practice. (26th February 2021) - de Pooter, Jacco; Billas, Ilias; de Prez, Leon; Duane, Simon; Kapsch, Ralf-Peter; Karger, Christian P; van Asselen, Bram; Wolthaus, Jochem
Abstract: With the rapid increase in clinical treatments with MRI-linacs, a consistent, harmonized and sustainable ground for reference dosimetry in MRI-linacs is needed. Specific for reference dosimetry in MRI-linacs is the presence of a strong magnetic field. Therefore, existing Code of Practices (CoPs) are inadequate. In recent years, a vast amount of papers have been published in relation to this topic. The purpose of this review paper is twofold: to give an overview and evaluate the existing literature for reference dosimetry in MRI-linacs and to discuss whether the literature and datasets are adequate and complete to serve as a basis for the development of a new or to extend existing CoPs. This review is prefaced with an overview of existing MRI-linac facilities. Then an introduction on the physics of radiation transport in magnetic fields is given. The main part of the review is devoted to the evaluation of the literature with respect to the following subjects: beam characteristics of MRI-linac facilities; formalisms for reference dosimetry in MRI-linacs; characteristics of ionization chambers in the presence of magnetic fields; ionization chamber beam quality correction factors; and ionization chamber magnetic field correction factors. The review is completed with a discussion as to whether the existing literature is adequate to serve as basis for a CoP. In addition, it highlights subjects for future research on this topic.